Exploring the common mechanisms of motion-based visual prediction - Hu, Dan (2024)
The ability of the visual system to predict the spatiotemporal properties of a moving object (e.g., when and where a moving ball will be) is essential to daily life. Motion-based visual prediction may serve not only for explicit anticipation about the future but also for compensation for neural transmission delays in visual processing when perceiving motion. We asked whether there are generic mechanisms of motion-based visual prediction for motion perception in the thesis.